Brand-building: the creative city A critical look at current concepts and practices - VICARI, SERENA (Strumenti per la didattica e la ricerca, 2010)
The aim of this book is to contribute to a critical assessment of the literature on the creative city and to a clarification of some of the many questions that remain unanswered. It is a collection of essays which, in the first part, addresses concepts and theories of urban development, city marketing and branding, presented as a framework in which the discourse of the creative city is embedded. In the second part, four case studies of cities considered to be emblematic of cultural industries (Manchester, Berlin, Dublin, and a comparative study of Milan and London) serve to illustrate the social production of creativity in specific urban contexts.